2015
DOI: 10.1155/2015/828023
|View full text |Cite
|
Sign up to set email alerts
|

An IoT-Based Home Energy Management System over Dynamic Home Area Networks

Abstract: A smart grid (SG) has attracted great attention due to recent environmental problems. SG technologies enable users, such as energy system operators and consumers, to reduce energy consumption and the emission of greenhouse gases, by changing energy infrastructure more efficiently. As a part of the SG, home energy management system (HEMS) has become increasingly important, because energy consumption of a residential sector accounts for a significant amount of total energy consumption. However, a conventional HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…the way to execute the IoT systems, the integration of the WSN with the IoT is a new generation of the M2M (Machine to Machine) Communication and the Scientific research played a valuable role in the Collecting data from sensors and use them in IoT applications [10][11][12][13]. In [14], the authors suggested a system for monitoring which is based on IoT technology, this system uses a triple-level context for offering the awareness services designed contextualization, throughout employing an opensource software and hardware. That test was carried out by employing two scenarios as a smart household based on an IoT-based Monitoring System (IMS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…the way to execute the IoT systems, the integration of the WSN with the IoT is a new generation of the M2M (Machine to Machine) Communication and the Scientific research played a valuable role in the Collecting data from sensors and use them in IoT applications [10][11][12][13]. In [14], the authors suggested a system for monitoring which is based on IoT technology, this system uses a triple-level context for offering the awareness services designed contextualization, throughout employing an opensource software and hardware. That test was carried out by employing two scenarios as a smart household based on an IoT-based Monitoring System (IMS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…), Then, the specified behaviors (such as load management, demand response, etc.) can be operated by using the Open ADR communication protocol between the terminal units and DN [3,29].…”
Section: Terminal Unitsmentioning
confidence: 99%
“…In [14], Internet of Things (IoT)-based home vitality the executives framework proposed with lightweight photovoltaic (PV) framework over powerful home territory systems, which bolsters the development of home scalable, reusable, and interoperable energy management method. They proposed methods with lightweight PV framework over powerful home territory systems, which bolsters the development of.…”
Section: Related Workmentioning
confidence: 99%